PERANCANGAN SISTEM INFORMASI PENYEWAAN MOTOR BERBASIS WEB - Dupi Salvanera Hutabarat; Riyan Latifahul Hasanah (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
In the ever-evolving digital era, businesses are required to adapt to technological advances and changes in consumer behavior. One sector significantly impacted is transportation services, particularly motorcycle rentals. In Indonesia, the high demand for mobility makes motorcycles a primary choice for many, even though not everyone owns a private vehicle. This opens up opportunities for motorcycle rental businesses like Jakarte Motorcycle Rental. Currently, the rental process is still carried out manually via WhatsApp, which presents challenges in data management and service efficiency. This research aims to design and build a web-based motorcycle rental information system that can simplify the booking process, record transactions, and manage customer data in a structured and efficient manner. This system is expected to reduce communication errors, accelerate customer response, and improve service quality. The method used in this research is prototyping, which allows system development through the stages of initial prototyping, evaluation with users, and continuous improvement until the system meets needs. The implementation of this system is expected to improve the speed, accuracy, and documentation of transactions, as well as strengthen Jakarte Motorcycle Rental's competitiveness in the increasingly competitive vehicle rental industry.